The effect of smoking and physical activity level on exercise capacity in older adults - Wiatrak, Adrian; Mosiejczuk, Hanna; Szylińska, Aleksandra; Rył, Aleksandra; Turoń-Skrzypińska, Agnieszka; Maziarz, Agata; Rotter, Iwona (Journal of Education, Health and Sport, 2018)
Introduction: Exercise capacity is highly age-dependent and influenced by factors such as physical activity level and smoking. The aim of the study was to analyze the relationship between physical activity level, smoking and exercise capacity in people over 60 years of age. Materials and methods: The study involved 100 participants (50 female and 50 male) over 60 years of age (mean age 68.2 years). Based on the answers provided to a questionnaire about smoking and physical activity level, participants were divided into four groups: exercising non-smokers, exercising smokers, non-exercising non-smokers, and non-exercising smokers. Each group consisted of 25 subjects. Exercise capacity was measured using the 6-minute walk test and the Borg scale. Results: Intergroup comparison showed statistically significant differences between the average results of each group, both in the 6-minute walk test (p=0.010) and on the Borg scale (p<0.001). There was a positive correlation between the number of cigarettes smoked and the Borg score in the exercising smokers group (p<0.001). In both exercising groups there was a correlation between amount of physical activity per week and the results of the 6-minute walk test (p<0.001). In the same test, the mean results differed between the two sexes (p<0.001). Conclusions: In the studied population (aged over 60), non-active individuals and smokers had significantly lower exercise capacity than those who exercised regularly or did not smoke.